Find the inverse of f(x) = (3x - 6)/2

First, imagine that f(x) is written as y: 

y = (3x -6)/2

swap the variables over so you write y as x and x as y:

x = (3y - 6)/2

Next, solve for x (try and get the y on its own on the right hand side)

2x = 3y - 6

2x + 6 = 3y

(2x + 6)/3 = y

Finally, swap the x and y back over to receive your answer!

f(x)' = (2x + 6)/3

where f(x)' is the inverse of f(x)

Answered by Arantxa B. Maths tutor

9758 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

y = 2t^2, and x = 3t^3 - 2. Find dy/dx in terms of t.


A curve has equation y = 2x^5 + 5x^4 1 . (a) Find: (i) dy/ dx [2 marks] (ii) d^2y/ dx^2 (b) The point on the curve where x ¼ 1 is P. (i) Determine whether y is increasing or decreasing at P, giving a reason for your answer.


Differentiate e^x^2


Differentiate the function y = 26 + x - 4x³ -½x^(-4)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences